The Thirteenth Number: Then, There / Here and Now Število trinajst: takrat, tam / tukaj in zdaj - Thompson, Tok (Studia mythologica Slavica, 2015)
The number thirteen has several strong connotations in a number of diverse cultures. What is surprising, and puzzling, are the similarities of associations (the moon, women’s magic, omens, etc). This paper attempts a cross-cultural view of the number thirteen, and arrives at a hypothetical explanation to account for the widespread occurences of the phenomena. Several cultures have been investigated, but the ones in which thirteen is an “ominous” number are revealed to use, or have used, lunar-solar calendars. My hypothesis is that the number thirteen’s connotations derive ulitmately from a natural, and naturally observable regularity– the 12.41 lunations per solar year. Hence, cultures with a lunar-solar calendar are forced to reckon with an odd thirteenth month every year, and this month is, in this hypothesis, what has given the number thirteen its unique and widespread cultural properties.